PELATIHAN MANAJEMEN REFERENSI BERBASIS MENDELEY UNTUK PENINGKATAN LITERASI DIGITAL AKADEMIK MAHASISWA UNIVERSITAS PATOMPO MAKASSAR - Hastuti, Diah Retno Dwi; Andriani, Shadry; Adys, Himaya Praptani; Kamaruddin, Citra Ayni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2025)
The development of digital technology has resulted in an increased emphasis on students' academic literacy skills, particularly in the management of scientific references. However, preliminary observations suggest that 80% of students at Patompo University in Makassar are unfamiliar with reference management applications such as Mendeley and continue to use manual methods, which can potentially result in citation errors and plagiarism. A community service programme was implemented in the form of reference management training using Mendeley. The objective of this programme was to improve students' understanding, technical skills, and awareness of academic ethics. The implementation methods employed in this programme comprised lectures, question and answer sessions, simulations, and hands-on practice, with an emphasis on installation, metadata management, automatic citation, and bibliography compilation. Post-training reflections demonstrated that 90% of participating students experienced a significant increase in digital literacy, confidence in using the application, and commitment to its continued use. This finding indicates that practical training is an effective method for cultivating a culture of ethical and responsible scientific writing.